Relationship between locomotive syndrome, frailty and sarcopenia: Locomotive syndrome overlapped in the majority of frailty and sarcopenia patients. Issue 6 (6th April 2021) - Ide, Koichiro; Banno, Tomohiro; Yamato, Yu; Hasegawa, Tomohiko; Yoshida, Go; Yasuda, Tatsuya; Arima, Hideyuki; Oe, Shin; Mihara, Yuki; Ushirozako, Hiroki; Yamada, Tomohiro; Watanabe, Yuh; et al.
Abstract : Aim: The relationship between locomotive syndrome (LS), frailty and sarcopenia is unclear. This cohort study investigates the epidemiology of the three conditions and examines the relationship between them. Methods: The participants were 337 Japanese adults aged ≥60 years who had undergone a healthcare checkup. LS, frailty and sarcopenia were assessed using the Geriatric Locomotive Function Scale, the Kihon Checklist and the Asian Working Group for Sarcopenia criteria, respectively. The epidemiological investigation and correlations of the three concepts were examined. Results: In total, 212 participants (63%) were women. The participants' mean age was 76 years (range 60–94 years). The average Geriatric Locomotive Function Scale total score was 11.4 ± 11.2, and Kihon Checklist was 4.72 ± 3.97. A total of 202 (59.9%) participants met one of the criteria; 190 (56.9%) were diagnosed with LS, 77 (22.6%) with frailty and 26 (7.7%) with sarcopenia; and 70 out of 77 (90.1%) of frailty patients and 21 out of 26 (80.1%) of sarcopenia patients were included in LS. The relationship between the total score, subcategorical scores and survey items for each was investigated. Activities of daily living, physical function and mental status showed a strong correlation with all concepts. However, nutrition of frailty patients and muscle mass of sarcopenia patients did not correlate with other factors. Conclusions: LS overlapped with frailty and sarcopenia. LS criteria might be useful as the best tool to screen older persons who would be at risk for requiring care in the near future. However, nutrition status could only be assessed by frailty and muscle mass by sarcopenia. Geriatr Gerontol Int 2021; 21: 458–464 .